Intractable acute ischaemic priapism occurring secondary to newly commenced olanzapine. Issue 3 (31st March 2019) - Farag, Matthew; Goad, Jeremy; Temelcos, Catherine
Abstract : We present a case of intractable acute ischaemic priapism occurring secondary to newly commenced olanzapine. It demonstrates rapid intervention in a stepwise approach aiming to restore penile flaccidity in order to prevent chronic damage to the corpora cavernosa. After an unsuccessful conservative approach, our patient underwent two formal distal penile shunt procedures with no effective penile detumescence. Subsequently, bilateral proximal penile shunts were performed comprising a right corpus cavernosum to corpus spongiosum anastomosis and a left saphenous vein to left corpus cavernosum anastomosis. The patient remained an inpatient for observation, and detumescence was gradually achieved over several days after this procedure. However, follow-up revealed erectile dysfunction, and it was explained to the patient that he was unlikely to achieve further erections and that a penile implant was the only realistic option.